Impacto de las practicas estudiantiles en el bachillerato tecnico: Impact of internships on the development of work skills in technical high school - LEON ALVARADO, LEYDA; Mina Quiñonez, Kitty Johanna; Segress García, Hevia (Revista Minerva, 2025)
The implementation of student internships in Technical High School is essential for developing job skills, but it faces significant limitations. There is a disparity in the quality and access to these internships between public, semi-public, and private institutions, raising concerns about educational equity. Although designed to bridge theory and practice, internships often fall short due to the disconnect between educational institutions and companies. A critical challenge is the refusal of many companies to allow students to intern in areas related to their technical training. This not only frustrates students but also undermines the educational purpose of internships, preventing them from acquiring relevant skills. Furthermore, agreements between institutions and companies often remain on paper, with little effective communication and genuine commitment. In light of this situation, it is urgent to rethink linkage strategies, promoting more effective dialogue and supervision mechanisms that ensure compliance with agreements. Only real collaboration between education and the business sector will guarantee that internships fulfill their purpose, creating a skilled workforce prepared for the future.